2014
DOI: 10.1186/1471-2377-14-33
|View full text |Cite
|
Sign up to set email alerts
|

Association between neuromyelitis optica and tuberculosis in a Chinese population

Abstract: BackgroundA number of reports have described the presence of tuberculosis (TB) in neuromyelitis optica (NMO) patients. However, a definite association between the two conditions has not been conclusively demonstrated.MethodsTo investigate the association between NMO and TB in a Chinese population, we performed a retrospective review of hospital records of NMO patients, control patients and tuberculosis meningitis (TBM) patients from January 1, 1995 to December 31, 2011.ResultsThe frequency of preceding/simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…LETM are seen rarely in childhood MTB, and holocord LETM has been reported in only one patient. [ 3 ] To the best of our knowledge, our patient is the second case. In Sahu's study, four MTB adult patients have been reported with LETM without holocord.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…LETM are seen rarely in childhood MTB, and holocord LETM has been reported in only one patient. [ 3 ] To the best of our knowledge, our patient is the second case. In Sahu's study, four MTB adult patients have been reported with LETM without holocord.…”
Section: Discussionmentioning
confidence: 92%
“…The appearance through magnetic resonance imaging (MRI) of spinal cord lesions and serum NMO-IgG positivity plays a central role in NMO diagnose. [ 1 2 3 ] Different studies in children with NMO have reported a wide range of AQP4-IgG seropositivity (7%–80%). Nevertheless, 10%–40% of patients diagnosed with NMO remain seronegative for AQP4 antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…At present the association between NMOSD and TB remains unconfirmed, with the literature largely reporting individual cases and small case series from localised regions, with or without identified control groups. Furthermore, Li et al reported the largest case series to date (88 patients) and did not demonstrate a significant increased incidence of TB in their Chinese population 18. Finally, a small prospective controlled trial of antituberculous treatment for managing steroid refractory NMO suggested these drugs could improve outcome in NMO, an intriguing suggestion which requires further research 19…”
Section: Discussionmentioning
confidence: 98%
“…An association between NMOSD and TB has been reported over the past 50 years 6 14–22. Silber et al 15 described eight patients with pulmonary TB and myelitis or optic neuropathy without evidence of central nervous system TB: six developed NMOSD, one an acute necrotising myelopathy and one an optic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous reports mention a correlation between TB and NMO, a recent report failed to find a significant correlation. [ 8 9 ]…”
Section: Discussionmentioning
confidence: 99%